FORMULATION AND TESTING OF ANTI DANDRUFF HAIR TONIC LEAF EXTRACT OF GEDONG MANGO (Mangifera indica L.var.Gedong) AGAINST MUSHROOMS Pityrosporum ovale - Yayan Rizikiyan; Lela Sulastri; Yuniarti Falya; Hudzaifah Famera Fosanda; Atiqoh Nurul Hakim; Rima Yulia Senja (Universitas Muhammadiyah Magelang, 2023)
Gedong mango plant (Mangifera indica L.var.Gedong) is a plant that has potential as herbal medicine, especially in its leaves because it contains many secondary metabolites such as flavonoids, saponins, gallic tannins, catecat tannins, quinones and steroids or triterpenoids which can be used as antioxidants, antimicrobial and dandruff. This study aims to gedong mango leaf extract concentrations of 5%, 7%, and 10% in hair tonic preparations and to test the antidandruff activity. Gedong mango leaf simplicia (Mangifera indica L.var.Gedong) was extracted using the Microwave Assisted Extraction (MAE) method with Natural Deep Eutectic Solvents (NADES) sodium acetate dan lactic acid solvents with a molar ratlactic1:3. Hair tonic preparations are made in three formulas with the active ingredient of mango gedong leaf extract at a concentration of 5%, 7%, and 10%. Evaluation of hair tonic pr, separation air tonic preparation evaluation includes organ anoleptic, homogeneity, pH, and viscosity and eststy test of hair tonic anti-dandruffas carriedtestt by the healthy method against the fungus Pityrosporhealthyvale. Hair tonic of mango gedong leaf extract with concentrations of 5%, 7%, and 10% on organoleptic observations, homogeneity, pH, and viscosity met the requirements. The hair tonic has the potential as an antidandruff because it has antidandruff activity against the fungus Pityrosporum ovale and is classified as moderate to strong.